Hydrocarbon poisoning in children: 1-year retrospective study - Hatti, Sachin S; Uplaonkar, Vinod; Honnalli, Charanraj (Indian Journal of Child Health, 2018)
Context: Accidental hydrocarbon poisoning continues to be a major problem in children in India. Objectives: The objectives of the study were to study the demographics, clinico-laboratory profile of hydrocarbon poisoning in children admitted to our hospital from April 2015 to March 2016. Secondary Objective: The secondary objective of the study was to determine corelation between vomiting and development of pneumonia after hydrocarbon consumption. Materials and Methods: In this retrospective descriptive study, all children with the history of hydrocarbon consumption and admitted to the hospital during the study period were included in the study. The medical records of these children were reviewed retrospectively, data were recorded in a standard pro forma and were analyzed. Chi-square test was used for comparing differences between categorical variables. For interpretation of results, significance was adopted at p<0.05 at 95% confidence interval. Results: A total of 52 cases (thinner-15 and kerosene-37) were included in our study. Male: Female ratio was 1.4:1, with the mean age in years being 3.01±2. Most of them belonged to upper lower socioeconomic status (SES) and rural areas, 48 (92%) and 30 (57%), respectively. Most cases were seen in summer season 20 (38.3%). 14 children (23%) were asymptomatic, and 38 (77%) were symptomatic. Vomiting 35 (67.3%) was the most common symptom followed by cough 24 (46%) and fever 15 (28.8%). Four (7.9%) had altered sensorium and 2 (3.5%) had convulsions. Respiratory distress was seen in 30 (57.6%), tachycardia in 22 (42.3%), hypoxia in 21(40.3%), 4 (7.6%) had wheeze, and 18 (34.6%) had crackles. The mean duration of stay in hospital was ±40 h. The outcome was good, the improvement was seen with 48 (92.3%) and 4 left against advice. Conclusions: Most common age group was 1–3 years, with most of them, belonged to upper lower SES and rural background. Respiratory distress was the most common system involved followed by the central nervous system. Chemical pneumonitis was the only complication with the good outcome.